Role of Bedside Ultrasound in CMV Retinitis: A Case Report. (29th November 2012) - Westafer, Lauren; Nickels, L. Connor; Flach, Eike; De Portu, Giuliano; Stead, Latha Ganti
Abstract : We present a case of retinal detachment diagnosed by emergency department bedside ultrasonography in a patient with CMV retinitis. The indications and findings of ocular ultrasonography are discussed.